A Sociomedical–Medicolegal Analysis of Abnormal Uterine Bleeding Associated with Cervical Polyps: A Case Report - Yoas Pratama Simangunsong; Dadan Susandi; Ali Budi Harsono (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Abnormal uterine bleeding (AUB) is menstrual bleeding occurring outside pregnancy in women of reproductive age. Cervical polyps are a known cause of AUB and can lead to persistent bleeding and severe anemia. Management may pose sociomedical and medicolegal challenges, particularly for unmarried women, when treatment risks hymenal disruption.Case Illustration: A 38-year-old woman presented with recurrent chronic vaginal bleeding and severe anemia. Diagnosis was based on clinical history and a limited gynecological examination restricted to external inspection. Transabdominal ultrasonography suggested a cervical polyp, and laboratory testing revealed a hemoglobin level of 6.5 g/dL. The patient was hospitalized for blood transfusion and scheduled for vaginal cervical polyp extirpation. Initially, hysteroscopic polypectomy with referral to a tertiary hospital was proposed; however, the patient declined referral and opted for vaginal extirpation despite the potential risk of artificial hymenal disruption. The procedure included hymenal incision, cervical polyp extirpation, and uterine curettage, followed by planned hymenal reconstruction using 5-0 PGA sutures. Due to sociocultural and religious considerations, specific informed consent was obtained to address medicolegal aspects and document that any hymenal disruption was iatrogenic and medically indicated.Conclusion: This case underscores the importance of sociomedical and medicolegal considerations in managing AUB among unmarried women. Comprehensive informed consent is essential to protect patient autonomy and minimize legal risk for healthcare providers. Vaginal cervical polyp extirpation was successfully performed without causing permanent hymenal damage, yielding favorable clinical and sociocultural outcomes.Analisis Sosiomedis–Medikolegal terhadap Perdarahan Uterus Abnormal yangTerkait dengan Polip Serviks: Laporan KasusAbstrakPendahuluan: Perdarahan Uterus Abnormal (PUA) merupakan perdarahan menstruasi yang terjadi di luar kehamilan pada wanita usia reproduksi. Polip serviks merupakan salah satu penyebab PUA yang dapat menimbulkan perdarahan pervaginam persisten dan berisiko menyebabkan anemia berat. Penatalaksanaan kondisi ini dapat menimbulkan tantangan sosiomedikolegal, terutama pada perempuan yang belum menikah apabila tindakan medis berpotensi menyebabkan destruksi himen.Ilustrasi Kasus Seorang perempuan berusia 38 tahun datang dengan keluhan perdarahan pervaginam kronis berulang disertai anemia gravis. Diagnosis ditegakkan berdasarkan anamnesis dan pemeriksaan ginekologis terbatas melalui inspeksi luar. Pemeriksaan USG transabdominal menunjukkan dugaan polip serviks, sedangkan pemeriksaan laboratorium memperlihatkan kadar hemoglobin sebesar 6,5g/dL. Pasien dirawat untuk menjalani transfusi darah dan direncanakan menjalani ekstirpasi polip serviks secara per vaginam. Awalnya, pasien direncanakan menjalani histeroskopi dengan rujukan ke rumah sakit tersier, namun menolak rujukan dan memilih tindakan per vaginam dengan risiko robekan himen artifisial. Tindakan dilakukan melalui insisi himen, ekstirpasi polip serviks, dan kuretase kavum uteri, disertai rencana rekonstruksi himen menggunakan benang PGA No. 5-0. Mengingat pertimbangan sosial, budaya, dan agama, dilakukan informed consent khusus untuk melindungi aspek medikolegal.Kesimpulan: Kasus ini menegaskan pentingnya integrasi aspek sosiomedikolegal dalam penatalaksanaan PUA pada perempuan yang belum menikah. Informed consent yang komprehensif berperan penting dalam menjamin otonomi pasien dan melindungi tenaga medis. Penanganan berhasil dilakukan dengan ekstirpasi polip serviks secara per vaginam tanpa kerusakan himen permanen.